Comparative characteristics of antiarrhythmic and cardioprotective properties of some 7-ethyl-3-methyl-8-tioxanthin derivatives - Charishma, Parla (Запорізький державний медичний університет, 2021)
Methylxanthines of natural and synthetic origin are of biological and pharmacological interest. In dependence on the kind and place of substitution in one of xanthine rings, a large variety of pharmacological activities were reported.